Don't go with the 'FLO' – a student mobile texting service to enhance nursing student retention. (October 2016) - Boath, Elizabeth; Jinks, Annette; Thomas, Nigel; Thompson, Roy; Evans, Jayne; O'Connell, Phil; Taylor, Lisa
Abstract: Background: The review undertaken revealed that there is an abundance of literature concerning retention and the high levels of attrition among undergraduate students and of relevance here, nurse education. The study undertaken evaluated the use of mobile phone automated texts designed to provide information, support and reassurance to help alleviate the stress and anxieties that some undergraduate nursing students experience during the early phase of their studies and which can lead to some students leaving their programme. Objective: The objective of the study was to evaluate how use of automated mobile phone texts, using a system known as FLO, could usefully supplement pastoral support, as an intervention to reduce attrition among undergraduate nursing students. Design: A qualitative and quantitative evaluation was conducted using an open-ended questionnaire designed specifically for the study. Participants: The sample were two cohorts of undergraduate first year student nurses (n = 178). Of these 123 (69%) signed up to FLO and 77 (63%) completed the evaluation form. Methods: The evaluation form that was administered in a classroom situation one week after use of FLO had ceased. Data were analysed through use of a descriptive statistics and thematic analysis approaches. Results: A range of key themes emerged from the analysis including that text messages were helpful and supportive, increased a sense of belonging to the University and encouraged retention. There were some unresolved issues concerning the costs incurred by participants when sending reply text messages. Conclusions: It is concluded that FLO or use of similar mobile phone protocols can be a useful addition to approaches to improve undergraduate nursing student retention rates. Highlights: Helpful and supportive to nursing students Increase a sense of belonging to the University Encourage student retention and improve attrition rates